Key success factor ranking for intrafirm knowledge sharing: a Delphi method approach in the oil and gas industry - Silva, Thassia Conceição Almeida da (2017)
Knowledge and its propagation are unquestionably at the center of most, if not all, discussions on innovation, performance, as well as other elements related to firm success. Although the literature has proposed several key success factors for knowledge sharing, it has yet to explore how these factors rank in terms of importance from a firm nationality perspective. Through a Delphi Method approach, upstream professionals from four major multinational Oil & Gas firms (Brazilian, North American, Norwegian and French), with at least seven years of experience, ranked specific literature-based proposed factors for successful intrafirm knowledge sharing. There was a total of three rounds, where the first round had 41 participants, and the remaining two rounds (second and third) had 39 participants. On average, open door policy was the most relevant factors that lead to knowledge sharing among the four firms. In terms of the least relevant ones, acknowledgement and status were seen, on average, as factors less likely to lead to intrafirm knowledge sharing.